Negotiating Reform: Regulatory Heresy and the Cultural Politics of Public Service Delivery in Decentralized Indonesia - Arni, Arni (Baileo: Jurnal Sosial Humaniora, 2024)
This study examines the implementation of bureaucratic reform within the One Stop Integrated Services (PTSP) Department in Bone Regency, Indonesia. The main objective is to analyze how regulatory frameworks and community behavior intersect in shaping the outcomes of public service reform. Utilizing a descriptive qualitative approach, the research draws on primary data gathered through field observations, interviews, and documentation analysis. The study focuses on institutional arrangements governed by local regulations and the real-world practices within the PTSP service delivery system. The findings reveal that while the PTSP initiative has contributed to improved administrative efficiency and the standardization of licensing procedures, its effectiveness is challenged by persistent informal practices. In Bone Regency, social norms and community behaviors—typical of a transitional or “prismatic” society—often diverge from formal regulations. A notable phenomenon identified in this context is “regulatory heresy,” where citizens voluntarily offer additional incentives to expedite service, thus creating tension between formal bureaucratic standards and local cultural expectations. The novelty of this study lies in its critical analysis of how informal societal practices interact with formal public sector reforms, highlighting the complexities of achieving good governance in decentralized and culturally diverse settings. The research recommends strengthening institutional integrity mechanisms and promoting civic education to foster behavioral change among both service providers and recipients. These insights contribute meaningfully to the discourse on public administration, governance, and social transformation in developing regions.